KAJIAN MODUL BIMBINGAN PERKAWINAN UNTUK CALON PENGANTIN DAN FONDASI KELUARGA SAKINAH BACAAN MANDIRI CALON PENGANTIN PERSPEKTIF FILSAFAT HUKUM KELUARGA ISLAM IBNU ‘ĀSYŪR - Avi Afian Syah; Ilham Bustomi; Faqihuddin Abdul Kodir (Mahkamah : Jurnal Kajian Hukum Islam, 2023)
The implementation of marriage guidance is guided by book Marriage Guidance Module for Prospective Brides And The Foundation Of The Sakinah Family Independently Reading Of Prospective Brides. This research aims to answer the questions that become the formulation of the problem, namely: how does the thoughts of Ibnu ‘Āsyūr’s Islamic Family Law Philosophy in the Marriage Guidance Module for Prospective Brides And The Foundation Of The Sakinah Family Independently Reading Of Prospective Brides? And how is the relevance between the material in Marriage Guidance Module for Prospective Brides and The Foundation Of The Sakinah Family Independently Reading Of Prospective Brides with Ibnu ‘Āsyūr’s Islamic Family Law Philosophy in Maqāṣid Asy-Syarī’ah Al-Islāmiyyah to achieving the goal of marriage? This research uses library research, and uses a philosophical approach. The data analysis technique used is theoretical analysis using the book Maqāṣid asy-Syarī'ah Al-Islāmiyyah by Muḥammad Ṭāhir Ibnu 'Āsyūr. The conclusion obtained is that the writer finds the existence of Ibnu ‘Āsyūr’s Islamic Family Law Philosophy in the marriage guidance guide, in the form of four pillars that can support the formation of a strong marriage. Then, there is relevance between the two, so that if applied it can realize the goal of marriage, namely the formation of a harmonious family (sakīnah), and full of love (mawaddah and raḥmah).